LANGUAGE ENDANGERMENT: ILLUSTRATIONS FROM MARSABIT COUNTY, KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper interrogates the two opposing positions regarding the implications oflanguage loss to the survival of the relevant culture. While one position (cf.Miyaoka 2001:8; Thomason 2001:10) holds that language and culture require eachother for their continued survival, the other position (cf. Duenhauer and Duenhauer1998:76; Rigsby 1987:370) contends that the relationship between them is suchthat, in spite of their closeness, the loss of one does not necessarily lead to theloss of the other. The discussion is based on the linguistic situation in MarsabitCounty. The county is linguistically heterogeneous with over ten indigenous ethniccommunities who claim to be natives, and not (recent) immigrants. The languagesspoken by these inhabitants of the county are drawn from two major languagephyla: Afro-asiatic and Nilo-Saharan. A good number of these languages, however,are grappling with the threat of assimilation following contact with other(indigenous) languages whose speakers, apparently, exhibit some dominance(political, economical and statistical) over the rest. In particular, the paperexamines the threat posed to Elmolo and Rendille by Samburu, and to Burji, Waataand Konso by Borana. Using illustrations drawn from these cases of language shift,the paper demonstrates that the decline of linguistic diversity in Marsabit Countyhas a potentially impoverishing effect on the culture and by extension on thehuman development of the county.